Profiles and Predictors of Young Children's Digital Literacy and Multimodal Practices in Central China. Issue 6 (18th August 2022) - Dong, Chuanmei; Cao, Simin; Li, Hui
ABSTRACT: Research Findings : There are heated debates about the benefits and risks of using digital devices in the early years. This study explored the latent profiles and the associated predictors of digital literacy and multimodal practices in Chinese children to understand how children use and interact with digital devices at home. A total of 1953 parents were recruited from a province in central China and surveyed about their children's digital literacy and multimodal practices. The results indicated that: (1) all the children had access to a variety of digital technologies at home, with the most common digital practices being watching TV and using smartphones; (2) three latent classes of digital families were yielded: Low-level Profile (62.9% of the sample), Middle-level Profile (36.3%), and High-Level Profile (0.8%); and (3) child age, location and family annual income, home digital resources, parental beliefs, and parental mediation could significantly predict young children's digital literacy and their multimodal practice at home, respectively. Practice or Policy : The findings imply that there are remarkable within-group differences in early digital literacy and multimodal practices, primarily caused by family SES and parental factors. More attention should be paid to low SES families and parental education to narrow the digital divide in Chinese children.